Penerapan Metode Tallaqi pada Pembelajaran Tahfidz Al-Qur’an di MITTQUM Surakarta - Kinesti, Rakanita Dyah Ayu; Indriani, Tri; Sari, Novita Wulan; Muyassaroh, Naim (YASIN, 2023)
This research seeks to dispel the notion that face-to-face, full-time teacher-controlled learning is a classic and old-fashioned, well-proven approach. The selection of learning methods is not always based on the modernity of one's method, but applies to the characteristics of the material and the achievement of learning objectives. The Al-Qur'an memorization program or called the taḥfīẓ program is the flagship program in the curriculum at madrasas, one of which is MITTQUM. The type of research used is descriptive research, discussing the results of research findings by describing, elaborating and illustrating. This description is related to the flagship tahfidz program with the talaqqi method at MITTQUM. The researcher chooses a qualitative approach, because the researcher records findings or phenomena, then analyzes various documents found in the field, and finally writes a research report. The sample of this research was first class students of the Kuttab program at MITTQUM. The application of the talaqqi method goes through 3 stages of activity: initial activity in the form of prayer, preparation, addition of learning outcomes, and addition of material to be memorized. The main activity is starting with the teacher reading the letter followed by students, after reading the students independently memorize, after memorizing and are welcome to deposit their memorization in front of the teacher. closing activities in the form of punishment giving questions and providing motivation at the end of learning.